Indonesia's economic stabilization and development - Higgins, Benjamin Howard (New York : Institute of Pacific Relations, 1957)
This book is on the stabilization of Indonesia economy and it development.
An outgrowth of the author's Economic stabilization and development in Indonesia.
Bibliography: p. 142-146.
oo 12/8/18
Loans
Keywords: Indonesia